Robotic development environment for autonomous robotic systems - Shanbhag Raghavendra Nagaraj. (2009)
The project explores the Robotic Development Environment (RDE) studies; utilization of RDE for autonomous robot platform and developing the software device driver used in robotic research and embedded Systems. This report describes overall effort of project, feature of the project, which has been carried out in Advance Robotic Research Lab facility at NTU. As a part of my dissertation I tried my best to contribute for the research group as well as to satisfy my dissertation requirement. For Advance Robotics research Lab this project is another step in continuation of their heritage in contributing robotic research for robotic community.